Kebangkitan Agama di Tengah Peradaban Global - Aris Saefulloh (Al-Ulum, 2011)
Islam revealed to the world has a universal mission as the liberator of mankind from ignorance and powerlessness to build the happiness. To face the challenge of globalization, religion should be interpreted into five programs: first, the need to develop more than a social structural interpretation of individual interpretation as to understand the specific provisions in the Qur'an. Second is to change the way from subjective into objective way of thinking. Third is to shift the normative Islam to theoretical. Fourth, make the ideas evolved historically. Fifth, make specific formulations and empirical formulation of general revelation.